Differential histopathology of three bacterial diseases that affect the hepatopancreas of penaeid shrimp. - Varela-Mejías, Alexander; Peña-Navarro, Nelson (Agronomía Mesoamericana, 2015)
The objective of this work was to characterize the injuries caused by the acute hepatopancreatic necrosis; the necrotizing hepatopancreatitis, and septic hepatopancreatic necrosis in shrimp farming. The information collected from many literature sources associated with the observations made in tissue samples from infected shrimp was analyzed. Histopathology was used to process the affected tissues, analyzing tropism of injuries, the special and differential characteristics between these diseases. Among the main differences mentioned: the acute hepatopancreatic necrosis injuries move forward from the proximal areas of the tubules of the hepatopancreas to the distal regions and acute cell causing massive and intensive sloughing. In peels necrotising hepatopancreatitis tubular necrotic cells present with basophilic cytoplasm and granular appearance leading to granulom formation atrophy in the terminal phase; and finally the septic hepatopancreatic necrosis injury presents a randomly advance of injuries with pyknotic epithelial cell detachment, forming hemocytic and immediate inflammatory response. Distinguish between these diseases provides the possibility that, by histopathological analysis can make a differential diagnosis between them.